A novel miR-375-HOXB3-CDCA3/DNMT3B regulatory circuitry contributes to leukemogenesis in acute myeloid leukemia - Bi, Laixi; Zhou, Bin; Li, Haiying; He, Licai; Wang, Chunjing; Wang, Zhonggai; Zhu, Liqing; Chen, Mengqian; Gao, Shenmeng (BMC cancer, 2018)
Acute myeloid leukemia (AML) is a heterogeneous group of hematopoietic malignancies due to sophisticated genetic mutations and epigenetic dysregulation. MicroRNAs (miRNAs), a class of small non-coding RNAs, are important regulators of gene expression in all biological processes, including leukemogenesis. Recently, miR-375 has been reported to be a suppressive miRNA in multiple types of cancers, but its underlying anti-leukemia activity in AML is largely unknown. Quantitative reverse transcriptase PCR (qRT-PCR) was used to measure the expression of miR-375 and HOXB3 in leukemic cells and normal controls. Targets of miR-375 were confirmed by western blot and luciferase assay. Phenotypic effects of miR-375 overexpression and HOXB3 knockdown were assessed using viability (trypan blue exclusion assay), colony formation/replating, as well as tumor xenograft assays in vivo. The expression of miR-375 was substantially decreased in leukemic cell lines and primary AML blasts compared with normal controls, because DNA hypermethylation of precursor-miR-375 (pre-miR-375) promoter was discovered in leukemic cells but not in normal controls. Lower expression of miR-375 predicted poor outcome in AML patients. Furthermore, forced expression of miR-375 not only decreased proliferation and colony formation in leukemic cells but also reduced xenograft tumor size and prolonged the survival time in a leukemia xenograft mouse model. Mechanistically, overexpression of miR-375 reduced HOXB3 expression and repressed the activity of a luciferase reporter through binding 3'-untranslated regions (3'-UTR) of HOXB3 mRNA. Overexpression of HOXB3 partially blocked miR-375-induced arrest of proliferation and reduction of colony number, suggesting that HOXB3 plays an important role in miR-375-induced anti-leukemia activity. Knockdown of HOXB3 by short hairpin RNAs reduced the expression of cell division cycle associated 3 (CDCA3), which decreased cell proliferation. Furthermore, HOXB3 induced DNA methyltransferase 3B (DNMT3B) expression to bind in the pre-miR-375 promoter and enhanced DNA hypermethylation of pre-miR-375, leading to the lower expression of miR-375. Collectively, we have identified a miR-375-HOXB3-CDCA3/DNMT3B regulatory circuitry which contributes to leukemogenesis and suggests a therapeutic strategy of restoring miR-375 expression in AML.